Esperienza e cognizione incarnata nei processi di integrazione mentale: l'apporto dell'analisi poetico-cognitiva alla teologie - Barone, Christian (Gregorianum, 2024)
The article aims to introduce the branch of neuroscientific research that goes by the name of Cognitive Poetics, the purpose of which is to investigate the cognitive mechanisms (conceptual blending) involved in the enjoyment of a narrative text and that enable the reader/hearer to identify with the text, to actively participate in its process of signification by drawing on his or her own emotional, experiential, and cultural experience. The application of the toolkit offered by Cognitive Poetics to the Lucan parable of the Good Samaritan and other Gospel pericopes allows us to highlight the importance accorded by the synoptic narratives to the corporeality of Jesus. In particular, the "apocalyptic" connotation with which the evangelist Luke sketches the dimension of Jesus' "feeling" in his visceral participation in the suffering of the People and creation.